Feasibility, acceptability, and preliminary effects of the Join4Joy approach for older adults living in nursing homes: a multicentre mixed-methods feasibility study - Erika Karkauskiene; Laura Coll-Planas; Andrea Fuente-Vidal; Damaso Sanchez; Nadine Barth; Dhayana Dallmeier; José Luis Socorro-Cumplido; Maria Giné-Garriga; Paolo Caserotti; Guillaume Lefebvre; Javier Jerez-Roig (European Geriatric Medicine, 2026)
Abstract Purpose Nursing home residents increasingly enter care with advanced frailty, multimorbidity, and functional dependence, underscoring the need for engaging, adaptable physical activity (PA) programmes. Join4Joy is a co-created approach designed to promote movement and social connection among older adults through enjoyable activities. This study examined its feasibility, acceptability, and preliminary effects across five nursing homes in Spain, France, and Germany. Methods This multicentre mixed-method study (ClinicalTrials.gov: NCT06100835) was delivered in two phases. Residents aged ≥ 65 years participated in 12 weekly 60-min PA sessions. Feasibility was assessed through attendance, procedural indicators, data completion, and retention; acceptability was evaluated using participant satisfaction and qualitative feedback, while safety was monitored throughout. Quantitative assessments evaluated physical function (SPPB), daily functioning (modified Barthel Index), quality of life (EQ-5D-5L), PA and sedentary behaviour (IPAQ-SF, SBQ, accelerometry), perceived improvement (PGI-I), and enjoyment (PACES-SF). Qualitative interviews and focus groups explored participant experiences. Results Of 81 enrolled residents, 75 completed the intervention (retention = 92.6%). Attendance was high (73.8–95.0%), no adverse events occurred. Quantitative outcomes indicated small favourable or no changes in physical and daily functioning, quality of life, PA and sedentary behaviour, perceived improvement, and enjoyment. Qualitative themes highlighted enjoyment, social connection, confidence, and the value of tailored, playful activities, confirming high acceptability. Conclusion Join4Joy is safe, feasible to deliver, and well received, demonstrating the viability of a future definitive trial. Future large-scale evaluations should integrate holistic psychosocial metrics like enjoyment and social connection alongside biomedical outcomes to fully assess co-created PA approaches in long-term care geriatric settings.